The Impulsive Neutral Integro-Differential Equations with Infinite Delay and Non-Instantaneous Impulses - Usha, V.; Mallika Arjunan, M. (International Journal of Engineering and Technology, 2018)
In this manuscript, we work to accomplish the Krasnoselskii's fixed point theorem to analyze the existence results for an impulsive neutral integro-differential equationsÂ with infinite delay and non-instantaneous impulses in Banach spaces. By deploying the fixed point theorem with semigroup theory, we developed the coveted outcomes.Â Â Â